OTHORHINOLARYNGOLOGIC COMPLICATIONS OF ARVI IN FAMILY PRACTICE - K. A. Nikitin; M. A. Shavgulidze; E. B. Gerasimova (Медицинский совет, 2013)
Acute respiratory viral infections (ARVI) is generally understood as a number of clinically similar acute airborne infections characterized by inflammation of mucous membranes of respiratory tract, rarely associated with conjunctivitis or keratoconjunctivitis and moderate intoxication [1, 6, 12]. Currently there are over 200 strains of ARVI and flu viruses which belong to different groups (parainfluenza, adenovirus, rhinovirus, respiratory syncytial virus (RS), etc. [1, 10, 11]. ARVI is reportedly the most common infectious disease. It should be noted that in this country the flu and ARVI affects more people than all other infections altogether. Since 2005 the damage to the economy of Russia from the flu and ARVI equals 100 billion roubles annually [12].